Study on liquid-like SiGe cluster growth during co-condensation from supersaturated vapor mixtures by molecular dynamics simulation - Wang, Wen-Bo; Ohta, Ryoshi; Kambara, Makoto (Physical Chemistry Chemical Physics, 2022)
Based on the co-condensation processes in the Si-Ge system upon cooling, as determined by molecular dynamics (MD) simulation, we explored the mixed cluster growth dynamics and structural properties leading to the synthesis of liquid-like SiGe nanoclusters. The results indicated that the cluster size quickly increased to large clusters by the coalescence of transient small clusters in the growth stage during co-condensation. The transient clusters at different temperatures were verified to have slightly Si-rich compositions and liquid-like structures. The coalescence of such nanoclusters at high temperatures led to spherical clusters with homogeneous intermixing. However, irregularly shaped clusters with attached mixed parts were obtained owing to incomplete coalescence at low temperatures. Ge atoms tended to move to the cluster surface to exploit their energetically favorable state during the restructuring process, leading to slightly Ge-rich components on the cluster surface. The degree of intermixing for SiGe nanoclusters was related to cluster size. Generally, small clusters appeared to be more segregated during restructuring. Illustrations of the formation for the different shaped clusters with cooling.